CURRENT STATE OF AUTOMOTIVE LIGHTING EQUIPMENT WITH NON-REPLACEABLE LIGHT SOURCES ON BASIS OF LIGHT-EMITTING DIODE TECHNOLOGIES - S. P. Sernov; D. V. Balokhonov; T. V. Kolontaeva (Наука и техника)
The paper contains information on the current state of automotive lighting equipment. Different designs of automotive lighting devices, their merits and demerits are described in the paper. The paper includes a substantiation of expediency of developing light-emitting diode lighting and proposes recommendations about optimization of their design.